Job search website for illiterate users of Pakistan. Issue 2 (May 2017) - Khan, Iftikhar Ahmed; Hussain, Syed Sajid; Shah, Syed Zafar Ali; Iqbal, Tassawar; Shafi, Muhammad
Highlights: This study proposes a website to help illiterate users of Pakistan to search a job. The users do not need any external help while searching a job. The usability of the website is evaluated according to ISO 9241-11. The illiterate users were able to search jobs with effectiveness and efficiency. The users' age and experience with computers/mobiles did not affect the usability. Abstract: Illiteracy is a major hurdle in socio-economic development of Pakistan. Research in the Information and Communication Technology (ICT) can help in tackling this issue by developing solutions tailored for illiterate population. The work presented within this paper proposes a job search website for illiterate population of KPK province of Pakistan. The designed website does not require any human assistance while searching a job. Moreover, the website uses culturally relevant graphical and audio content. The usability of the website is tested according to the ISO-9241-11 specification. Furthermore, we have studied the effect of the participants' characteristics, i.e., their age, computer and mobile usage experience on the usability of the website. The results show that the participants found the website usable. Specifically, they could search suitable jobs with a minimal number of clicks and in less time as compared to the usual task completion rates reported throughout the literature. None of the participants' characteristics were found to be affecting the usability of the website. These results suggest a promising potential of ICT solutions for providing services to illiterate population of Pakistan.